2004
DOI: 10.1128/jb.186.24.8508-8515.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cold Adaptation in the Antarctic Archaeon Methanococcoides burtonii Involves Membrane Lipid Unsaturation

Abstract: Direct analysis of membrane lipids by liquid chromatography-electrospray mass spectrometry was used to demonstrate the role of unsaturation in ether lipids in the adaptation of Methanococcoides burtonii to low temperature. A proteomics approach using two-dimensional liquid chromatography-mass spectrometry was used to identify enzymes involved in lipid biosynthesis, and a pathway for lipid biosynthesis was reconstructed from the M. burtonii draft genome sequence. The major phospholipids were archaeol phosphatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 41 publications
3
127
0
Order By: Relevance
“…Nichols et al 37) have also identified unsaturated archaeol-and unsaturated hydroxyarchaeol-based phospholipids with glycerol and inositol as polar head groups by HPLC-MS in a psychrotrophic methanoarchaeon, Methanococcoides burtonii, isolated at Ace Lake in Antarctica. They reported that the unsaturated archaeol core contains one to five double bonds, although the location of the double bonds could not be determined.…”
Section: Allyl Ether Type Core Lipids From Methanopyrus Kandleri and mentioning
confidence: 99%
See 3 more Smart Citations
“…Nichols et al 37) have also identified unsaturated archaeol-and unsaturated hydroxyarchaeol-based phospholipids with glycerol and inositol as polar head groups by HPLC-MS in a psychrotrophic methanoarchaeon, Methanococcoides burtonii, isolated at Ace Lake in Antarctica. They reported that the unsaturated archaeol core contains one to five double bonds, although the location of the double bonds could not be determined.…”
Section: Allyl Ether Type Core Lipids From Methanopyrus Kandleri and mentioning
confidence: 99%
“…In fact, all of the hyperthermophilic Pyrococcus furiosus (optimum temperature, 98 C), 33) moderately thermophilic Methanothermobacter thermautotrophicus (65 C), 74) mesophilic Methanobacterium formicicum (37 C), 54) and Methanogenium cariaci (23 C) 54) have caldarcheaol-based polar lipids with a smaller amount of archaeol-based lipid. Unsaturated archaeol (geranylgeranyl group-containing archaeol) is present in psychrophilic Methanococcoides burtonii 37) that can grow at 2 C as well as in hyperthermophilic Methanopyrus kandleri (98 C). 34) The same ether lipids of archaea can be utilized at both high and low temperatures because of their liquid crystalline phase and low permeability in a wide range of temperatures.…”
Section: Physiological Significance Of Archaeal Lipids-what Is a mentioning
confidence: 99%
See 2 more Smart Citations
“…Given the abundance and diversity of Archaea in cold environments (Karner et al 2001;Feller & Gerday 2003), especially in the oceans, our understanding of the genetics and physiology of coldadapted Archaea is surprisingly scarce . Some insights have been obtained on the level of protein structure and function (Schleper et al 1997;Thomas et al 2001;Siddiqui et al 2002), gene regulation (Lim et al 2000;DasSarma 2006), tRNA modification (Noon et al 2004), membrane lipid composition (Nichols et al 2004 ;Gibson et al 2005), proteomics (Goodchild et al 2004a(Goodchild et al , b, 2005Saunders et al 2005) and genomics (Saunders et al 2003) by studying coldadapted Archaea.…”
Section: Introductionmentioning
confidence: 99%